A Comparative Analysis of the Digital Euro, Digital Ruble, and Digital Yuan in Different Aspects - Belov, German; Jedlinský, Jakub; Šváb, Patrik; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The bachelor's thesis is devoted to the comparative analysis of the selected aspects of the CBDC projects that belong to the European Central Bank, the Central Bank of Russia and the People's Bank of China. This work aims to identify each project's five most significant components in the different aspects, including Motivations & Objectives, Challenges & Risks in Development and Implementation, and Design Features, followed by a comparison that highlights similarities and differences between the identified components. The thesis consists of four chapters. The first chapter provides the theoretical underpinnings of the CBDC concept. Moreover, the chapter delineates the aspects of CBDC that are the focus of this study and gives their general components. Besides, the chapter covers the basic status of the CBDC projects under study. The second chapter focuses on identifying the five components of the motivations and objectives aspect for each project, followed by a comparison that highlights similarities and differences. The third chapter is dedicated to identifying each project's five components of the Risks and Challenges aspect, followed by a comparison that highlights the similarities and differences between the components. The fourth chapter identifies each project's five components of the Design Features aspect, followed by a comparison that highlights similarities and differences.
Vedoucí práce: Jakub Jedlinský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses